The Knower Gazes of teachers: struggles for legitimacy between established and newly qualified teachers in South African schools - Hlatshwayo, Philip (My University, 2020)
The South African education system is in a state of crisis. In a mostly dysfunctional education system which is characterized by inequalities, poor standards and poor performance, newly qualified teachers (NQTs) have been positioned as essential actors that can bring about change and transformation. The integration of NQTs into schools is gaining considerable attention recently as the national rollout of an induction programme for NQTs is planned. In light of the induction programmes for NQTs, it is essential to understand the struggles that NQTs face in their transition into the workplace. Previous research work on the struggles that NQTs face in their integration focused on assimilation, positioning the challenges NQTs face on the difficulties of assimilating into the environment, and adopting the prevalent culture and values. However, previous research work failed to address the underlying principles of legitimacy between NQTs and established teachers as actors whose ‘knower gazes’ view the practices of teaching from different standpoints. The purpose of this study is to explore the extent to which knower gazes legitimize NQTs and established teachers’ teaching practices in different ways. It will do this by analysing the ways in NQTs and experienced teachers respond similarly or differently to common dilemmas that teachers face in their classroom practices. The study adopts Legitimation Code Theory (LCT) as a conceptual and analytic framework for this study. It compares the constellations of meaning held by NQTs and established teachers in relation to their views of what is valued and should inform teaching practices. The research data was collected through six individual interviews and a focus group with participants from a historically disadvantaged school in Daveyton, Gauteng. The findings show that NQTs and established teachers occupy different stances with respect to the importance of knowledge for practice, relations to power, authority and control within school contexts, and in relation to teachers’ responsibilities. Findings illustrate that there are code clashes between the stances valorized by NQTs and established teachers concerning teaching practices. The findings suggest that NQT participants tended to place greater legitimacy in a principled and structured framework for practice. In contrast, participants who were established teachers tended to place the legitimacy of their teaching practices in the social community and the collective nature of the teaching profession. These differences have important implications for the induction of newly qualified teachers in the South African education system. Struggles between NQTs and established teachers are on the knowledge stances held about the practice rather than assimilation. The study positions the understanding of these clashes as essential in informing NQTs’ induction into the profession and contributing to the ongoing research into issues affecting the integration of NQTs
A dissertation submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the degree of Masters of Education by Dissertation, 2020
Keywords: Teachers-Training of-South Africa; Knowledge, Theory of